OBSERVATIONS ON THE INTRAOVARIAN OVA OF A FEW TACHYSURIDS FROM INDIAN WATERS - Menon, N Gopinatha (Indian Journal of Fisheries, 2011)
Three different groups of intraovarian ova, 'a', 'b' and 'c', are noticed inthe ovary of mouthbrooding tachysurid catfishes; the former two groups are smallnonyolked and reproductively nonfunctional and the last group is yolked, opaqueand functional. The group 'a' and 'b' ova are sequentially arranged, respectivelyin the oviducal and posterior region while the group 'c' ova occupies the anteriorthree-fourth of the ovarian cavity. There is a certain ratio in the number of ovaof the three groups, probably characteristic of each species. All the nonfunctionalova of the groups 'a' and 'b' and ripe functional group 'c' are spawned in a bunchand taken into the mouth of male, where only the group 'c' ripe eggs develop intoyoung ones.